Papel do gene PIWIL1 como possível agente no processo de transição epitélio-mesenquimal no câncer gástrico - PAIVA, Juliana Albuquerque Pinto (Universidade Federal do Pará, 2019)
The PIWI-LIKE PROTEIN 1 (PIWIL1) gene has emerged as an attractive target for gastric cancer, as studies have shown that PIWIL1 protein is expressed at increased levels in cancer tissues, stem cells and germ cells, but it has been shown to be absent in normal somatic tissues. This means that it could be a potential target for therapy, since most non-cancer cells would not be affected by cytotoxic effects. Although relevant information on the possible role of PIWIL1 in the carcinogenesis of gastric cancer is provided by the current literature, the molecular mechanisms involved in this carcinogenic process remain unclear. Therefore, in order to investigate the molecular mechanisms by which PIWIL1 confers advantages to cancer cells, CRISPR/Cas9 technology was employed in order to perform the permanent knockout of PIWIL1 gene in the AGP01 gastric cancer cell line. After knockout, experiments were carried out to evaluate the effect of this molecular alteration on the migration and invasion capacity of the cell line, as well as on the expression of genes involved in these two cellular mechanisms. The results demonstrated that PIWIL1 gene knockout caused a significant decrease in the migration capacity of AGP01 after 24 hours, as well as a significant decrease in the cell invasion capacity. In addition, gene expression results revealed 26 genes (five overexpressed and 21 hypoexpressed - when comparing the cell lines before and after knockout) that encode proteins involved in invasion and migration cellular processes. According to the current literature, nine of these 26 genes (DOCK2, ZNF503, PDE4D, ABL1, ABL2, LPAR1, SMAD2, WASF3 and DACH1) are possibly related to the mechanisms used by PIWIL1 to promote carcinogenic effects related to migration and invasion, since their functions are consistent with the observed modification (being overexpressed or hypoexpressed after knockout). Taken together, these data reinforce the idea that PIWIL1 should play a crucial role in the gastric cancer signaling pathway, regulating several genes involved in the migration and invasion processes, so its use as a therapeutic target can generate promising results in the treatment of this type of cancer.